2022
DOI: 10.3390/app12031155
|View full text |Cite
|
Sign up to set email alerts
|

Injury Incidence and Pattern in Elite Young Male and Female Trail Runners

Abstract: The aim of this study was to analyze the injury incidence in young trail runners according to the body region, type, mode of onset, and moment of occurrence, both in total and detailed by sex. Thirty-five male and sixteen female young elite trail runners, aged between 15 and 22 years, completed a questionnaire regarding the injury incidence in the last 2 years. Comparison of the proportions of the injury incidence within groups (all, male, and female runners) and between groups (male vs. female runners) was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
7

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 54 publications
0
4
0
7
Order By: Relevance
“…When one considers the scenario where head-loads are carried while walking through rugged mountain terrain, the possibility of poor medial–lateral proprioception could be responsible for lateral ankle sprains and falls (in the frontal plane), which does adversely affect the quality of life of the rural community dwellers. Krolikowski et al ( 2018 ) and Sanchez-Garcia et al ( 2022 ) reported that mountain hikers sustain a high incidence of ankle and knee sprains (in medial–lateral axis within the frontal plane), which were advocated as being the mechanism of falls. Insofar as the geographic location of iLembe District is in the mountainous region of KwaZulu-Natal, the aforementioned literature does support the premise that poor medial–lateral proprioception stability in the frontal plane could produce ankle pain and falls, causing injury to the lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…When one considers the scenario where head-loads are carried while walking through rugged mountain terrain, the possibility of poor medial–lateral proprioception could be responsible for lateral ankle sprains and falls (in the frontal plane), which does adversely affect the quality of life of the rural community dwellers. Krolikowski et al ( 2018 ) and Sanchez-Garcia et al ( 2022 ) reported that mountain hikers sustain a high incidence of ankle and knee sprains (in medial–lateral axis within the frontal plane), which were advocated as being the mechanism of falls. Insofar as the geographic location of iLembe District is in the mountainous region of KwaZulu-Natal, the aforementioned literature does support the premise that poor medial–lateral proprioception stability in the frontal plane could produce ankle pain and falls, causing injury to the lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…La prevalencia de lesiones se ha descrito en función de la región anatómica o según el diagnóstico de lesión, incluso según el tipo de tejido afectado (Tabla 3). Así, en función de la región anatómica, las lesiones más prevalentes son, en primer lugar, en el tobillo con un 49,5% y 32% en diferentes estudios (Sánchez-García et al, 2022y González et al, 2021. La rodilla ha sido otra de las regiones más reportadas, ocupando la primera posición entre las lesiones musculo-esqueléticas, como en el estudio de Gajardo et al (2021) con una prevalencia del 34,9% en hombres y un 30% en mujeres; según Hsu et al (2020) con un 38%, y para Viljoen et al (2021aViljoen et al ( , 2021b con un 29,8% y 26,5%, respectivamente (Tabla 3).…”
Section: Prevalencia De Lesiones En Carreras De Trail Runningunclassified
“…Con respecto al diagnóstico, las lesiones musculo-esqueléticas más reportadas son las tendinopatías, con un 27,8% (Viljoen et al, 2021a) y 18,9% (Sánchez-García et al, 2022). La lesión del tendón de Aquiles (12,8%), también ha sido una de las más prevalentes (Hespanhol et al, 2017), así como los esguinces articulares, con una prevalencia del 43,2% (Sánchez-García et al, 2022), y 20,5% (Viljoen et al, 2021a). Concretamente, el esguince de tobillo es el que más se ha descrito, con valores de 28,6% (Vernillo et al, 2016).…”
Section: Prevalencia De Lesiones En Carreras De Trail Runningunclassified
“…During 20–42 km mountain running races, a 5-season study reported that most musculoskeletal injuries occurred in the ankle (32%), followed by the knee (14%) (17). Finally, in a 2-year retrospective study conducted with under 22 years elite trail runners, Sanchez et al (28) reported that ankle sprains were the most reported injuries (49.5% of all injuries). Currently, prevention strategies in sport consist in understanding interactions between internal (predisposing the athlete) and external (the sports' demands and context of activity) risk factors (6,29).…”
Section: Introductionmentioning
confidence: 98%
“…Compared with road races, which are usually run on a smooth surface, trail running implies hilly running on uneven terrain (with stones and tree roots, for example). Regulation of locomotor behavior during uphill and downhill running has been extensively studied on treadmill and in real conditions (for a review refer to 28). Specifically in trail running, course duration, variation in gradients, training status, and running technique (forefoot/rearfoot strike pattern) have been determined as factors influencing the severity of muscle damage and neuromuscular alterations (24,32).…”
Section: Introductionmentioning
confidence: 99%